Harmonization of EU legislation in the field of compensation for damage caused by minors - Cherniak, Olena (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
In the article, the author examines the peculiarities of the harmonization of EU legislation in the field of compensation for damage caused by minors. The author analysed the soft law of the EU in this area and focused on national regulation in the researched area. The author focused on the fact that today there is still a conditional question about whether the harmonization of tort law of the EU is possible and desirable. Harmonization of tort law requires not only a formal legal basis, but also a substantial justification. The conclusions are summarized that the content (depth) of harmonization should contribute to the improvement of the creation and functioning of the EU internal market. And therefore, by harmonizing acts within the EU, it is necessary in a certain way to move away from those colourful norms that take place among the legal regulation of compensation for damage caused by minors in 27 EU member states. The author concluded about the importance of soft law in the context of regulating the studied relations. The author focused attention on the need to standardize uniform approaches to the concepts of minors and minors. The author supported the idea of revising the age of demarcation of such categories. The article examines examples of EU countries, where three models of legal regulation of compensation for damage caused by minors are defined. The author is convinced of the expediency of studying the legal experience of the EU as a whole and its individual countries from the point of view of borrowing the best practices for settling compensation for damage caused by a minor. The author emphasizes the need to adhere to the trends in debate in this area, where it is likely to go beyond the legal systems of the EU member states and expand the legal perspective towards all European countries, including Ukraine, which, according to quite realistic estimates, can quickly become a full member of the EU.